Auditing Canadian Curricula for the Prevalence of Personal-Finance Related Terms Using Text-Frequency and Distant-Reading Software Tools - Armstrong, Wes, Mr. (Scholarship@Western, 2019)
This quantitative research study explores each set of provincial curriculum documents (save for Quebec) for the frequency of user-selected personal-finance based terms. The data from each province is compared and examined to answer: which provincial curriculum mentions user-selected personal-finance terms most frequently; how many words/pages are between each term mention, and how many personal-finance terms appear in the top 500 words in each curriculum. The research found that Prince Edward Island’s curriculum documents contained the most searched-for terms (at least one mention). Further, money (British Columbia and Newfoundland) and entrepreneur (Nova Scotia) are the only two searched-for personal-finance terms among the 500 most frequently-mentioned words in each set of curriculum-based corpora and appear approximately once every 16.5 pages in each of those respective sets of curriculum documents. This project uncovers a wealth of information about the extent to which personal-finance related terms appear in each province's curricula via software-based tools. However, further research is encouraged to corroborate these findings. Furthermore, follow-up classroom-based observations would provide useful qualitative evidence to triangulate the quantitative data and enhance the inquiry into the state of personal-finance education in Canadian schools. Moreover, those interested in utilizing the data sets from this project in future research need to be aware that text-based term mentions are not necessarily indicative of in-class practices. Thus, further research needs to be conducted to gain a deeper understanding of school-based personal-finance learning, and complementary projects examining the impact of text mentions on human behaviour are encouraged.